Assessment of Workforce Systems Preferences/Skills Based on Employment Domain. Issue 1 (2nd January 2020) - Jaradat, Raed; Stirgus, Erin; Goerger, Simon R.; Buchanan, Randy K.; Ibne Hossain, Niamat Ullah; Ma, Junfeng; Burch, Reuben
Abstract: Given the growing demand for a workforce with an understanding of system of systems, there is a need to assess an individual's systems thinking skills. This research was undertaken to address this need by measuring an individual's inclination to work on complex system problems based on their systems thinking score. This article investigates the correlation between employment domains and an individual's systems thinking preferences/skills. Results of this research show that each employment domain is significantly different in their systems thinking preferences/skills profiles as well as significantly different in how the employment domains perceive change and their system's worldview.